Pengembangan gear dengan proses additive manufacturing berbasis lattice structure dengan dimensi variasional - Vynna Alviolina Indriyana; Gandjar Kiswanto; Ridho Irwansyah (BKS-TM Indonesia, 2025)
Gears are fundamental components in mechanical systems, where reducing weight without compromising strength is a key engineering challenge. This study introduces a multi-material gear with a lattice structure fabricated by Additive Manufacturing (AM). The design integrates an outer gear of Ti-6Al-4V for high strength and wear resistance with an inner gear of 316L stainless steel for structural support. Weight reduction was achieved by generating a diamond wire cube lattice with variable strut diameters, optimized using stress distribution data from finite element analysis and clustering with the K-means algorithm. Structural analysis through ANSYS Explicit Dynamics and fatigue simulations confirmed that stresses remained below the ultimate tensile strength of both materials, ensuring reliable service life. Thermal analysis with CFD indicated a maximum operating temperature of 64.1 °C, within the typical gear range of 50–140 °C. The proposed design reduces gear mass by 34.8% compared to a solid model, demonstrating the feasibility of multi-material AM with lattice optimization for lightweight and durable gear applications.